RETINAL ANGIOMATOUS PROLIFERATION DIAGNOSIS: A Multiimaging Approach. Issue 12 (December 2016) - Ravera, Vittoria; Bottoni, Ferdinando; Giani, Andrea; Cigada, Mario; Staurenghi, Giovanni
Abstract : Purpose: To identify signs occurring more frequently in retinal angiomatous proliferation (RAP) lesions compared with other types of choroidal neovascularization (CNV) in age-related macular degeneration. Methods: In this cross-sectional retrospective study, 30 patients were evaluated. These signs were correlated with the type of CNV: shunting of blood flow to the lesion by fluorescein angiography, late leakage by indocyanine green angiography, intraretinal cysts and retinal pigmented epithelium interruption along the retinal pigmented epithelium detachment with a hyperreflective oval area by spectral domain optical coherence tomography, and presence of reticular pseudodrusen by infrared light. Results: Shunting of blood flow was found in 56% of RAP, whereas it was absent in 100% of other CNVs. Late leakage in indocyanine green angiography occurred in all RAP cases, while it was found in 7% of other CNVs. Intraretinal cysts were detected in 100% of RAP cases and in 14% of other CNVs. Retinal pigmented epithelium interruption along the retinal pigmented epithelium detachment was evident in 93% of RAP cases and in 15% of other CNVs. Reticular pseudodrusen were present in 87% of RAP cases and in 21% of other CNVs. Conclusion: All the signs investigated were strongly associated to RAP lesions. A multimodal imaging approach may help differentiating subtypes of neovascularization. Abstract : Using a multiimaging approach to facilitate a proper differential diagnosis, the authors investigated signs occurring more frequently in retinal angiomatous proliferations compared with other types of choroidal neovascularization.